Evaluation of different parasitological techniques in the diagnosis of canine helminthiasis - Novaes, Marcelle Temporim; Martins, Isabella Vilhena Freire (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Novaes M.T. & Martins I.V.F. [Evaluation of different parasitological techniques in the diagnosis of canine helminthiasis.] Avaliação de diferentes técnicas parasitológicas no diagnóstico de helmintoses caninas. Revista Brasileira de Medicina Veterinária, 37(Supl.1):71-76, 2015. Laboratório de Parasitologia, Hospital Veterinário, Universidade Federal do Espírito Santo, Rua Alto Universitário, s/n, Guararema, Alegre, ES 29500-000, Brasil. E-mail: marcelle_temporim@hotmail.com Were collected 100 fecal samples from dogs from August 2014 to April 2015 from the Zoonosis Control Center (CCZ) of Cachoeiro de Itapemirim-ES. These were sent to the laboratory of Parasitology of the Veterinary Hospital of UFES, and analyzed in duplicate by the techniques of Kato-Katz, Hoffman, TF-Test Modified/Dog and Willis in order to evaluate the technique that present higher sensitivity, convenience and lower expenses with materials for parasitological diagnosis. Statistical analysis was performed using Fisher’s exact test and kappa the 5% significance level. Together they showed up 68 positive samples, 31, 34, 26 and 62 for technical Kato-Katz, Hoffman, TF-Test and Willis respectively. The results showed that the use of Willis technique should be adopted as the standard for egg Ancylostoma spp., since the techniques Kato-Katz, Hoffman and TF-Test showed a low sensitivity for diagnosis of this parasite, and technic of Hoffman should be used as standard for Toxocara spp. In relation to convenience and lower expenses, Willis technique, should be preferred, because the runtime and the microscope slide reading is fast, requiring only the use of a supersaturated solution.